A novel CO2- and SO2-tolerant dual phase composite membrane for oxygen separation1. Issue 33 (28th April 2015) - Cheng, S.; Søgaard, M.; Han, L.; Zhang, W.; Chen, M.; Kaiser, A.; Hendriksen, P. V.
<x xml:space="preserve">Abstract</x> Here we report a novel, cheap, non-toxic, CO2- and SO2-stable dual phase composite oxygen transport membrane (Al0.02Ga0.02Zn0.96O1.02–Gd0.1Ce0.9O1.95−δ) for oxygen separation.